Dıversıté Démocratıque Et Constıtutıon Républıcaıne. Pour Une Paıx Perpétuelle Avec Kant Et Habermas - Faloukou, Dosso (European Scientific Journal, ESJ, 2016)
The variety of the democratic realities creates of the suspicions for universal model of democracy that lies in the implementation of a republican constitution favorable to the promotion of perpetual peace. It is necessary to create the conditions for company management rationalization on constitutional grounds, those extensions of freedom, citizenship. Any democracy can’t be achieved without it. The republican constitution democracy becomes the embodiment of the compass promoted by Kant and Habermas. When, in their quest for perpetual peace, Kant advocates the republican constitution in a clean cosmopolitan space in the Republic, Habermas opts for a Democratic rule of law.